Internet‐based interventions for postpartum depression: A systematic review and meta‐analysis - Ting‐Yu Mu; Yu‐Hong Li; Ri‐Xiang Xu; Jun Chen; Ya‐Ya Wang; Cui‐Zhen Shen (Wiley, 2021)
Abstract Aim To determine the efficacy of Internet‐based interventions in decreasing the prevalence of postpartum depression in perinatal women. Design This review was conducted according to the standards outlined in the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Methods We performed a systematic meta‐analysis of randomized controlled trials on the efficacy of Internet‐based interventions for postpartum depression. Studies (2008-2018) were identified through a search conducted on PubMed, EMBASE and the Cochrane Library. Risk ratios or weighted mean differences with 95% confidence intervals were calculated using a fixed‐effects model or a random‐effects model. Stata software 11.0 was used to perform the meta‐analysis. Results Most of the seven eligible studies were randomized controlled trials. The random‐effects model indicated that Internet‐based interventions significantly improved postpartum depression (d = 0.642, N = 7). Attrition rates ranged from 4.5%-86.9% and from 0%-87.1% for the intervention and control groups, respectively.